A new review and karyological analysis of Leiolepis belliana and L. boehmei (Reptilia, Agamidae) from a population in southern Thailand. Issue 4 (2nd October 2018) - Jantarat, Sitthisak; Patawang, Isara; Buatip, Somsak; Thongroy, Pimonrat; Kraiprom, Thaintip; Tanomtong, Alongklod
ABSTRACT: The diploid number of both Leiolepis belliana and L. boehmei was 2 n = 2 x = 36. In addition, the karyotype of the two species exhibited many conserved characteristics, including six pairs of macrochromosomes and 12 pairs of microchromosomes, the type and size of the macrochromosomes, and the position of the secondary constriction and nucleolar organizer region (NOR). However, while the position of the NOR region was identical in both species, in L. belliana it was found on both chromosomes of the first pair, and in L. boehmei it appeared on only one of the chromosome of the first pair, classified as 1a. No cytologically distinguishable sex chromosome was observed in either species. The karyotype formulae of L. belliana and L. boehmei were identical: 2 n (36) = L m 4 + M m 6 + S m 2 + 24 microchromosomes.